Hypertension and life expectancy among Japanese: NIPPON DATA80 - Turin, Tanvir Chowdhury; Murakami, Yoshitaka; Miura, Katsuyuki; Rumana, Nahid; Kita, Yoshikuni; Hayakawa, Takehito; Okamura, Tomonori; Okayama, Akira; Ueshima, Hirotsugu (Hypertension research, 2012)
Life expectancy (LE) is a measure that describes the health status of a population. The few published studies that have examined the impact of hypertension on LE were predominantly performed in Western populations. The effect of hypertension on LE has not been reported in an Asian population. Thus, we examined the impact of hypertension on LE in the Japanese population, which has the highest LE worldwide. The abridged life table method was applied to calculate the LEs of both normotensive and hypertensive men and women aged 40-85 years. Hypertensive participants were categorized as having either stage 1 or stage 2 hypertension. Age-specific mortality rates across different groups were estimated using the person-year method based on the follow-up data from a representative Japanese population in a national survey (NIPPON DATA80). The proportion of hypertensive patients in the baseline survey was 50.5% for men and 41.4% for women. The LE of 40-year-old men and women was 41.7 years and 48.7 years, respectively, in normotensive participants and 39.5 and 45.8 years, respectively, in hypertensive participants. The LE difference between normotensive and hypertensive participants was 2.2 years for men and 2.9 years for women. LE decreased with increasing stages of hypertension. Similar patterns of LE, with respect to blood pressure (BP) status, were observed in all index ages and for both genders. At the population level, hypertension leads to decreased LE and affects both genders similarly. Our findings highlight the importance of preventing high BP and the consequences of hypertension in Japanese population.